-x-y=1

Add x to both sides of the equation.

-y=1+x

Multiply each term in -y=1+x by -1

Multiply each term in -y=1+x by -1.

(-y)⋅-1=1⋅-1+x⋅-1

Multiply (-y)⋅-1.

Multiply -1 by -1.

1y=1⋅-1+x⋅-1

Multiply y by 1.

y=1⋅-1+x⋅-1

y=1⋅-1+x⋅-1

Simplify each term.

Multiply -1 by 1.

y=-1+x⋅-1

Move -1 to the left of x.

y=-1-1⋅x

Rewrite -1x as -x.

y=-1-x

y=-1-x

y=-1-x

y=-1-x

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Reorder -1 and -x.

y=-x-1

y=-x-1

Find the values of m and b using the form y=mx+b.

m=-1

b=-1

The slope of the line is the value of m, and the y-intercept is the value of b.

Slope: -1

y-intercept: -1

Slope: -1

y-intercept: -1

Choose 0 to substitute in for x to find the ordered pair.

Replace the variable x with 0 in the expression.

f(0)=-(0)-1

Simplify the result.

Multiply -1 by 0.

f(0)=0-1

Subtract 1 from 0.

f(0)=-1

The final answer is -1.

-1

-1

The y value at x=0 is -1.

y=-1

y=-1

Choose 1 to substitute in for x to find the ordered pair.

Replace the variable x with 1 in the expression.

f(1)=-(1)-1

Simplify the result.

Multiply -1 by 1.

f(1)=-1-1

Subtract 1 from -1.

f(1)=-2

The final answer is -2.

-2

-2

The y value at x=1 is -2.

y=-2

y=-2

Create a table of the x and y values.

xy0-11-2

xy0-11-2

Graph the line using the slope and the y-intercept, or the points.

Slope: -1

y-intercept: -1

xy0-11-2

Graph -x-y=1